Ecos da vida: A construção do terapeuta de famílias: a prática clínica sob a lente das vivências na família de origem - Cramer, Carla Teresinha (2006)
Family Therapy as a field of work has undergone diverse changes over its 50 years of existence, in relation both to the body of theories it comprises and the process entailed until it effectively evolved into a family-oriented therapy. Until the late twentieth century, during the 80s, the most common approaches in that area were intervention-based and those supported by modern paradigms, which employed the application of theories as a tool and the acquisition of techniques. The therapist would take on the role of a specialist. It was finally considered a dialogic activity when Second-Order Cybernetics, Social Constructivism and Constructionism concepts were brought into the therapy as such, and the therapist became the focal point of the subject at hand. Contributions made by scholars of Gender and Culture emphasise the importance of self-reflection, which should be practiced by the therapist to assure that his or her own life experiences, past or present, do not have a negative influence when counselling their patient-clients. The purpose of this study was to understand how the therapist s life experience acquired within the environment of his or her family of origin could influence their family counselling practice. The case study method was employed. The tools used to obtain relevant material were semi-structured interviews and genogram assessment of the mental health professional. Information yielded was analysed and divided into the following body of themes: Parentality, Conjugality, Fraternal Relationships, Gender and Culture. Another significant finding from this study is the current challenge posed by this field, e.g. the integration of different concepts originating from diverse approaches that comprise what is known as Family Therapy